Clinical characteristics of resistant hypertension evaluated by ambulatory blood pressure monitoring. (November 2014) - Kansui, Yasuo; Matsumura, Kiyoshi; Kida, Haruko; Sakata, Satoko; Ohtsubo, Toshio; Ibaraki, Ai; Kitazono, Takanari
Abstract Strict control of blood pressure is important to prevent cardiovascular disease, although it is sometimes difficult to decrease blood pressure to target levels. The aim of this study was to investigate the clinical characteristics of resistant hypertension evaluated by ambulatory blood pressure monitoring. One hundred in-hospital patients, whose 24-hour average blood pressure was higher than 130/80 mmHg even after treatment with more than three antihypertensive drugs, were included in the present analysis. Circadian variation of blood pressure was evaluated by nocturnal fall in systolic blood pressure. Average blood pressures of all patients were high in both daytime and nighttime, 150.0/82.9 and 143.8/78.2 mmHg, respectively. Twenty patients had been treated with hemodialysis or peritoneal dialysis. In 63 patients out of the other 80 patients (79%), estimated glomerular filtration rate (eGFR) was also decreased (<60 mL/min/1.73 m2). The patients classified into dipper, non-dipper, riser and extreme-dipper were 20%, 43%, 34% and 3%, respectively. In addition, in 17 patients whose eGFR was preserved, 12 patients showed a non-dipper or riser pattern, suggesting that it was difficult to account for this altered circadian blood pressure variation only by renal dysfunction. These results show that a large number of the patients with resistant hypertension suffered from renal dysfunction, although it was difficult to explain altered circadian blood pressure variation based on renal dysfunction alone.